Acute effect of 3 stretching techniques on sideward movements in tennis - Ricardo Martínez-Chicote; Gabriel Brizuela; Pedro Pérez-Soriano; Salvador Llana Belloch (Asociación Española de Ciencias del Deporte, 2016)
Stretching exercises are widely used as a part of the warm-up in sports, although stretching benefits are still questioned. The aim of this study was to analyze the acute effect of three stretching techniques performed during the warm-up, on typical tennis sideward movements. 20 tennis players (6 women and 14 men, aged 17.75 ± 1.7 years, weight 67.05 ± 10.07 Kg, height 173, 4 ± 10.12 cm) participated. The effect of three of the most popular stretching techniques (PNF, Static and Ballistic) as well as the absence of stretching during the warm-up was analyzed using a sideward movement test (Brown, Piorkowski, Roetert & Woods, 1995). Results showed the best performance time (p < 0.05) for the "absence of stretching" condition versus the other three conditions. There were no differences (p > 0.05) on performance time between the three conditions in which stretching was included during the warm-up. It can be concluded that to stretch (PNF, Static or Ballistic) during warm up reduces performance in sideward movements in tennis.